2019
DOI: 10.1186/s13054-019-2336-6
|View full text |Cite
|
Sign up to set email alerts
|

Lung fluid biomarkers for acute respiratory distress syndrome: a systematic review and meta-analysis

Abstract: BackgroundWith the development of new techniques to easily obtain lower respiratory tract specimens, bronchoalveolar lavage fluid and other lung fluids are gaining importance in pulmonary disease diagnosis. We aimed to review and summarize lung fluid biomarkers associated with acute respiratory distress syndrome diagnosis and mortality.MethodsAfter searching PubMed, Embase, Web of Science, and the Cochrane Library for articles published prior to January 11, 2018, we performed a meta-analysis on biomarkers for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 70 publications
0
27
0
3
Order By: Relevance
“…Plasminogen activator inhibitor-1 (PAI-1) is a pro-coagulant that is released by platelets and the endothelium in response to inflammation, damage, or ischemia and can be used as early marker for endothelial injury based on its inhibitory function of urokinase-like plasminogen activator (uPA) (38). Elevations of PAI-1 in bronchiolar lavage fluid is associated with experimentally-induced pulmonary fibrosis after thoracic radiation exposure (39) and in patients with lethal acute respiratory distress syndrome (40). Thus, the presence of PAI-1, uPA, and the high PAI-1/uPA ratio (>10) in perilymph may be an indicator for cochlear distress and damage.…”
Section: Discussionmentioning
confidence: 99%
“…Plasminogen activator inhibitor-1 (PAI-1) is a pro-coagulant that is released by platelets and the endothelium in response to inflammation, damage, or ischemia and can be used as early marker for endothelial injury based on its inhibitory function of urokinase-like plasminogen activator (uPA) (38). Elevations of PAI-1 in bronchiolar lavage fluid is associated with experimentally-induced pulmonary fibrosis after thoracic radiation exposure (39) and in patients with lethal acute respiratory distress syndrome (40). Thus, the presence of PAI-1, uPA, and the high PAI-1/uPA ratio (>10) in perilymph may be an indicator for cochlear distress and damage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in the literature have detected biomarkers of fibrogenesis in the bronchoalveolar fluid 24 h after the onset of ARDS that correlate with mortality. These include N-terminal pro-peptide of type III collagen, C-terminal pro-peptide of type I collagen, TGF-β, and alveolar fibroblasts and fibrocytes (24)(25)(26)(27). Fibrocytes have been shown to expand in the blood in the context of both physiologic wound repair and several diseases associated with fibrogenesis.…”
Section: Possible Biomarkers Of Disease Progressionmentioning
confidence: 99%
“…In the PI3K pathway, PKB can also stimulate the mammalian target of rapamycin (mTOR), resulting in the activation of STAT3 [28]. Moreover, evidence has revealed that stimulation of PKB/Akt, MAPK, STAT3, and NF-кB prompts a wide range of inflammatory responses and pathological states in different disorders such as severe pneumonia and ARDS [29,30] (Fig. 1).…”
Section: Il-6/il-6 Receptor Axis Bio-structure and Signalingmentioning
confidence: 99%